CBL-mediated AQP1 ubiquitination aggravates kidney-yang deficiency syndrome by promoting lipid metabolism dysregulation - Yifei Wang; Jun Yuan; Wenfang He; Nan Yang; Lanjun Fu; Juan Jin (European Journal of Medical Research)
Abstract Objective Kidney-Yang Deficiency Syndrome (KYDS) is associated with lipid metabolism dysregulation. This study aimed to investigate the effect of casitas B-lineage lymphoma (CBL)-mediated aquaporin 1 (AQP1) ubiquitination on KYDS. Methods The KYDS rat model was induced via intraperitoneal injection of hydrocortisone. Body weight, body temperature, sperm motility, serum hormone levels, organ indices, and histopathological changes of rats were evaluated. AQP1 was knocked down to detect the effect of AQP1 on lipid metabolism in KYDS rats. Immunofluorescence and immunoprecipitation were used to verify the relationship between CBL and AQP1, and CBL knockdown KYDS rats were constructed to test the effect of CBL on AQP1 ubiquitination. Results AQP1 expression was downregulated in KYDS rats. Knockdown of the AQP1 gene in KYDS rats resulted in decreased body weight, body temperature, sperm motility, and testicular index, along with increased renal index. It also resulted in changes of serum hormone levels and exacerbated pathologic changes. Additionally, AQP1 knockdown further suppressed lipid accumulation in KYDS rats, as evidenced by reductions in lipid droplets and the expression of lipid synthesis proteins. Intriguingly, elevated expression of CBL was observed in KYDS, and its knockdown inhibited the ubiquitin-mediated degradation of AQP1. The inhibition of CBL in KYDS improved lipid metabolism dysregulation, thereby ameliorating KYDS. Conclusion CBL-mediated AQP1 ubiquitination aggravates KYDS by promoting lipid metabolism dysregulation, offering promising insights for targeted therapeutic interventions.